2020
DOI: 10.1088/1361-6404/ab7831
|View full text |Cite
|
Sign up to set email alerts
|

Hermione and the Secretary: how gendered task division in introductory physics labs can disrupt equitable learning

Abstract: Physics labs provide a unique opportunity for students to grow their physics identity and science identity in general since they provide students with an opportunity to tinker with experiments and analyze data in a low-stakes environment. However, it is important to ensure that all students are benefiting from the labs equally and have a positive growth trajectory. Through interviews and reflexive ethnographic observations, we identify and analyze two common modes of work that may disadvantage female students … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 57 publications
3
49
0
Order By: Relevance
“…While a 50/50 split might sound equitable on the surface, as reported by previous work [17,[37][38][39][40], more so than in samegender groups it is not uncommon for students in mixedgender lab groups to engage in gendered task division in which men tend to do one type of work while women tend to do another. Thus, the mutuality of engagement associated with a "fair split" of the work is markedly different from, and may be less equitable than, the mutuality of engagement associated with an distribution of the learning activities in which each group member participates equally in all aspects of the work.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…While a 50/50 split might sound equitable on the surface, as reported by previous work [17,[37][38][39][40], more so than in samegender groups it is not uncommon for students in mixedgender lab groups to engage in gendered task division in which men tend to do one type of work while women tend to do another. Thus, the mutuality of engagement associated with a "fair split" of the work is markedly different from, and may be less equitable than, the mutuality of engagement associated with an distribution of the learning activities in which each group member participates equally in all aspects of the work.…”
Section: Discussionmentioning
confidence: 80%
“…We approached the problem in three ways: first, by asking students about the characteristics of an ideal lab partner; second, by investigating how students' perceptions of the distribution of the lab work between the partners (equal or unequal participation in all aspects of the lab) is related to self-reported changes in their interest and self-efficacy in physics; and third, by assessing whether gender might play a role in the relationship between lab work distribution and self-efficacy. This quantitative work is designed to complement qualitative analysis reported elsewhere [17].…”
Section: Introduction and Frameworkmentioning
confidence: 99%
“…Open-ended (i.e., interactive or constructive) lab instruction can offer students more choice and agency as they engage with the material. Open-ended labs can benefit students in multiple ways, from developing more expert-like attitudes towards experimentation [6] to developing positive science identities [7][8][9]. Supporting students to enact their agency, however, is more than simply removing structure.…”
Section: Introductionmentioning
confidence: 99%
“…Instructional physics labs are typically interactive learning environments, but research has shown that student interactions can be a source of inequity in their learning [e.g. [1][2][3][4]. To understand the wide range of equitable and inequitable interactions among students, we build on a methodology to characterize the equity of student lab groups through bids and the notion of inchargeness [5].…”
Section: Introductionmentioning
confidence: 99%
“…A person who controls the conversation more than others, however, can be considered generally in charge. Because prior research has found inequitable gendered patterns in participation in lab activities [2,3,9,10], our research seeks to understand the relation between inchargeness, equity, and gender.…”
Section: Introductionmentioning
confidence: 99%